The Many Meanings of D-Day - Kate Delaney (European Journal of American Studies)
This essay investigates what D-Day has symbolized for Americans and how and why its meaning has changed over the past six decades. While the commemoration functions differently in U.S. domestic and foreign policies, in both cases it has been used to mark new beginnings. Ronald Reagan launched his “morning again in America” 1984 re-election campaign from the Pointe du Hoc, and the international commemorations on the Normandy beaches since 1990 have been occasions to display the changing face of Europe and the realignment of allies.